2014
DOI: 10.1002/lary.24285
|View full text |Cite
|
Sign up to set email alerts
|

Motion sensitivity and caloric responsiveness in vestibular migraine and Meniere's disease

Abstract: Objectives We examined whether scores on a motion sensitivity questionnaire (MSQ) could distinguish between vestibular migraine (VM) and Meniere's disease (MD). As a secondary goal, we examined whether scores on the MSQ correlated with results from caloric testing. Study Design This study administered a telephone questionnaire to subjects who met clinical criteria for vestibular migraine, Meniere's disease, and controls. Methods A MSQ was administered to 20 subjects meeting American Academy of Otolaryngolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 34 publications
4
34
0
1
Order By: Relevance
“…This can be explained by the small number of tested patients with bilateral deficit. The higher MSS in vestibular patients without vestibular loss (nVL), in particular for vestibular migraine, confirmed the existing findings [7,18].…”
Section: Discussionsupporting
confidence: 86%
“…This can be explained by the small number of tested patients with bilateral deficit. The higher MSS in vestibular patients without vestibular loss (nVL), in particular for vestibular migraine, confirmed the existing findings [7,18].…”
Section: Discussionsupporting
confidence: 86%
“…Motion sickness susceptibility scores after diagnosis (MSC scores) were 1.5 times higher in Meniere's disease patients compared with controls. This is similar to that reported in a telephone survey by Sharon & Hullar [6]. Compared with controls, Meniere's disease patients also suffered from more headaches and migraine, increased VDD, higher SWID4 scores, and increased syncope.…”
Section: Discussionsupporting
confidence: 77%
“…A telephone survey of patients with MD suggested that they had elevated motion sickness susceptibility compared to controls but not as elevated as patients with vestibular migraine [6]. Here, we aimed to increase our understanding by screening a large population of Meniere's disease patients and healthy controls with an online version of a validated motion sickness susceptibility questionnaire (MSSQ) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We found no evidence of a strong relationship between gain or phase thresholds and detection or discrimination thresholds measured at 0.5 Hz, suggesting that psychometric results may indeed provide information not available from reflexive measurements alone. Recent data suggest, for example, that subjects with migraine have altered perceptual thresholds to tilt although they do not necessarily have different VOR responses than normal controls (Lewis et al 2011; Sharon and Hullar 2013). The finding that there is no close correspondence between perceptual values and the VOR supports the concept that the two may indeed carry different information about peripheral vestibular function leading, likely dictated by higher-order processes (Merfeld et al 2005a, 2005b).…”
Section: Discussionmentioning
confidence: 99%